The Effect of Instructor Pedagogic Competency and Learning Motivation on Vocational Skills of Training Participants at BLK Cilegon City - Tharisa Ayu Pranovcy; Syadeli Hanafi; Dadan Darmawan (Universitas Muhammadiyah Makassar, 2023)
This study aimed to analyze and determine the effect of instructor pedagogic competence and learning motivation on the vocational skills of trainees at BLK Cilegon City. The population consists of trainees who are members of the heavy equipment engineering profession, including forklift operator vocational training, excavator operator vocational training, and crane operator vocational training, totaling 120 people, with sample numbers of 92 people. The background of this research is due to the instructor’s pedagogic competence, learning motivation, and vocational skills that have yet to be evenly distributed to all training participants. Data collection is done by distributing questionnaires, observation, and documentation. The research method uses descriptive analysis with a quantitative approach. The data is then processed using the SPSS-25 application. The study results show that: 1) the instructor's pedagogical competence has a very significantly affects the trainees’ vocational skills. 2) learning motivation has a very significantly affects the trainees’ vocational skills. 3) the instructor’s pedagogical competence and learning motivation simultaneously has a very significantly affects the trainees’ vocational skills at BLK Cilegon City.Keywords : Instructor Pedagogic Competence, Learning Motivation, Vocational Skills